PENILAIAN PRODUKTIVITAS TERNAK DAN KESESUAIAN POTENSI PAKAN TERNAK DI KAWASAN AGRO-EKOLOGIS - Makarius Bajari Bajari; Deny Anjelus Iyai; Johan Frederik Koibur; Lukas Yowel Sonbait; Frandz Rumbiak Pawere (Jambura Journal of Animal Science, 2022)
The purpose of this study was to determine the portrait of livestock production in the neighborhood environment as a basis for livestock commodity development and animal husbandry development, to determine the needs and potential of animal husbandry development in Waropen Regency.The method was done using descriptive study by using desk study and reference review. The object of observation was livestock production and forages yielded from crops. The results of the studyshowed that portrait of livestock production is not optimal yet, marked by the low number of livestock production on each district of several commodities. Animal feed needs to be intensified. Thus technical assistance needs to be provided.